Pengembangan Sistem ERP Modul Inventory Management Pada Kantor Perwakilan PT. BGA Group - Eka Prasetyaningrum; Benny Setyawan (SMATIKA JURNAL : STIKI Informatika Jurnal, 2023)
Entering the industrial era 4.0, companies are required to be able to survive with all kinds of risks faced. PT. Bumitama Gunajaya Agro Group is one of the plantation companies and palm oil mills in Central Kalimantan. PT. BGA Group has a representative office located in Sampit City. In managing inventory of goods at the Representative Office at PT. BGA Group has been computerized but has not been well integrated. For data collection of requests for goods from the farm, vendor data collection, incoming and outgoing goods, and shipping goods must still be recorded one by one into Microsoft Excel. Therefore, it is necessary to have a system that can make it easier for employees to make requests, record and even search for the data needed so that the ERP inventory module can be a solution. For the system development method use the Agile method with testing black box. Based on the test results, the existence of an inventory system can make work easier and can shorten the time in the process of managing company data.